Limits and opportunities to community health worker empowerment: a multi-country comparative study - Kane, Sumit; Kok, Maryse; Ormel, Hermen; Otiso, Lilian; Sidat, Mohsin; Namakhoma, Ireen; Nasir, Sudirman; Gemechu, Daniel; Rashid, Sabina Faiz; Taegtmeyer, Miriam; Theobald, Sally; Koning, Korrie de (© 2016 Elsevier Ltd, 2016)
This article was published in Social Science and Medicine [© 2016 Elsevier Ltd.] and the definite version is available at: https://www.ncbi.nlm.nih.gov/pubmed/27459022